Boron concentration and isotopic composition of halite from experiments and salt lakes in the Qaidam Basin - Liu, W.G.; Xiao, Y.K.; Peng, Z.C.; An, Z.S.; He, X.X. (Geochimica et cosmochimica acta, 2000)
The concentration and isotopic abundance of boron in salt can be used to trace paleosalinities and depositional environments for marine and non marine evaporites. However, the mechanism of incorporating boron into halite during evaporation of salt lake brines is subject to dispute, and there have been few studies of boron concentrations and isotopic compositions during this process due to the low boron concentration in halite. A group of evaporation experiments from artificial solutions and salt lake brines have been analyzed in this study. The results of boron concentration and isotopic analyses demonstrate that the boron in halite comes mainly from fluid inclusions, with a lesser amount from coprecipitation. The isotopic fractionation factors between the brine and halite are from 0.9857 to 1.0000 for the evaporation experiments, and 0.9945 to 1.0009 for natural samples from the salt lake. The δ 11B values of halite from the Qaidam Basin salt lakes vary from −4.7 to 25.8‰, compared to −4.7 to 31.4‰ in the salt lake brines. These values are controlled by the boron isotopic composition of the boron sources, pH values and Na/Ca ratios in the salt lake brines. The variation of boron isotopes in halite may be used to trace the hydrochemical evolution and paleoevaporation environment in salt lakes.